Assessment of oral health status and tobacco-related habits among the employees of North-West Karnataka Road Transport Corporation (NWKRTC), Belagavi City - A Cross-Sectional Study (International Journal of Occupational Safety and Health, 2022)
Introduction: Transport workers have a very haphazard and incongruent schedule which makes it difficult for them to follow proper oral hygiene practices. The prevalence of tobacco habits is also found to be high due to their long periods of work and constant stress. This study aimed to assess the oral health status and tobacco habits of the government bus drivers and conductors of NWKRTC, Belagavi City, Karnataka. Methods: A descriptive cross-sectional study was conducted on 451 Government Bus drivers and other employees of NWKRTC who gave consent for the study. WHO Oral Health Assessment Form 2013 was used to record the oral health status and a self-designed, validated questionnaire was employed for recording the oral hygiene practices and tobacco-related habits. Descriptive statistics and Chi-Square was used for statistical analysis.   Results: The mean age of the employees of NWKRTC is 43.55 years and there are 414 males as compared to only 37 females. The mean DMFT score was 5.55±3.08. 228 of them had some kind of tobacco habit with guthka (25.9 percent) being the most prevalent one. 57 employees had manifestations of leukoplakia and OSMF. There was an association between tobacco habits and oral mucosal lesions as well as the DMFT score.Conclusion: The Oral Health Status of the Government employees of NWKRTC is poor. It is further compounded by the high prevalence of tobacco habits and associated lesions and it is a problem that needs to be addressed immediately.